2020
DOI: 10.3390/min10080680
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade Flake Graphite Deposits in Metamorphic Schist Belt, Central Finland—Mineralogy and Beneficiation of Graphite for Lithium-Ion Battery Applications

Abstract: More than 40 m length of drill cores were collected from four boreholes drilled by Geological Survey of Finland (GTK) and Outokumpu Oy in high-grade metamorphic rocks of Rautalampi and Käypysuo, Central Finland. The hosted rocks of the graphite mineralization were mica–quartz schist and biotite gneiss. The graphite-bearing rocks and final concentrated graphite powder were studied with petrographic microscope, scanning electron microscope (SEM-EDS), Raman spectroscopy, and X-ray analysis (XRD and XRF). A majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The industrial production of natural graphite for LiBs applications involves several steps, starting with extraction of the mineral, followed by processing (such as grinding and purification), and finishing with the refinement of the final product. [11] Currently, the market offers a variety of graphite for LiBs applications, where various production steps (such as shaping, coating, and surface treatments) are employed to ensure quality (e. g., carbon coating of the graphite particles in order to reduce surface area and further increase conductivity). However, the increasing demand for high energy density under stressful operative conditions (such as low temperatures and high charging current densities) represents a significant challenge for standard graphite anodes.…”
Section: Introductionmentioning
confidence: 99%
“…The industrial production of natural graphite for LiBs applications involves several steps, starting with extraction of the mineral, followed by processing (such as grinding and purification), and finishing with the refinement of the final product. [11] Currently, the market offers a variety of graphite for LiBs applications, where various production steps (such as shaping, coating, and surface treatments) are employed to ensure quality (e. g., carbon coating of the graphite particles in order to reduce surface area and further increase conductivity). However, the increasing demand for high energy density under stressful operative conditions (such as low temperatures and high charging current densities) represents a significant challenge for standard graphite anodes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the grade of the flake graphite ore is quite low, posing challenges to its direct utilization. To satisfy industrial manufacturing demands, flake graphite needs to be purified by multistage grinding and multistage flotation beneficiation processes [2][3][4], such as seven grinding, eight flotation, nine grinding, and ten flotation processes. These beneficiation processes can improve the grade of flake graphite; however, the process is long and complex, and it is straightforward to damage the graphite structure on large scales.…”
Section: Introductionmentioning
confidence: 99%
“…Graphite in Precambrian crustal rocks has been reported worldwide, including in Sri Lanka [5], India [6], Mozambique [7], Madagascar [8] and Greenland [9]. In Scandinavia, graphite is a common mineral in Early Proterozoic terranes and occurs widely in the 2.0 Ga Svecokarelian of Sweden and Finland [10][11][12], the Paleoproterozoic crust of north Norway and Finland [13][14][15][16][17] and the Sveconorwegian Bamble lithotectonic domain of south Norway [18]. Strauss et al [19] showed that the enrichment of carbonaceous material occurred worldwide at 2.0-2.…”
Section: Introductionmentioning
confidence: 99%